2001
DOI: 10.1111/1468-2389.00177
|View full text |Cite
|
Sign up to set email alerts
|

On the Construct Validity of Integrity Tests: Individual and Situational Factors as Predictors of Test Performance

Abstract: Although integrity tests are widely applied in screening job applicants, there is a need for research for examining the construct validity of these tests. In the present study, a theoretical model examining the causes of destructive behavior in organizational settings was used to develop background data measures of individual and situational variables that might be related to integrity test scores. Subsequently, 692 undergraduates were asked to complete these background data scales along with (a) two overt int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 35 publications
(76 reference statements)
0
41
0
Order By: Relevance
“…As mentioned previously, narcissism is linked to lower supervisor ratings of integrity and a higher propensity to commit white-collar crime (Blair et al, 2008;Blickle et al, 2006;Mumford, Connelly, Helton, Strange, & Osburn, 2001). Moreover, recent research using business students found a negative relationship between narcissism and moral decision making (Brown, Sautter, Littvay, Sautter, & Bearnes, 2010).…”
Section: Future Directions the Role Of Narcissism In Other Managementmentioning
confidence: 82%
“…As mentioned previously, narcissism is linked to lower supervisor ratings of integrity and a higher propensity to commit white-collar crime (Blair et al, 2008;Blickle et al, 2006;Mumford, Connelly, Helton, Strange, & Osburn, 2001). Moreover, recent research using business students found a negative relationship between narcissism and moral decision making (Brown, Sautter, Littvay, Sautter, & Bearnes, 2010).…”
Section: Future Directions the Role Of Narcissism In Other Managementmentioning
confidence: 82%
“…Mumford et al (2001) found that individual characteristics, including narcissism and power motives, were associated with scores on both overt and personality-based tests. Situational characteristics, such as alienation and negative peer-group exposure, were also associated with scores on the two test types and were more strongly related to test scores than were individual characteristics-leading to questions about whether integrity tests identify enduring individual characteristics, which is their intent, or more-malleable situational characteristics.…”
Section: Associations Among Measuresmentioning
confidence: 96%
“…Several researchers had found that leader narcissism was negatively related to integrity and ratings of interpersonal performance (Blair, Hoffman, Helland, 2008;Helland, Blair, 2005;Kets de Vries, Miller, 1985;Mumford, Connelly, Helton, Strange, Osburn, 2001). Meanwhile Van Dijk and De Cremer (2006) found that narcissistic managers were more self-serving than their counterparts, with an inclination to allocate scarce organizational resources to themselves, and even to the extent as being linked to white-collar crimea (Blickle, Schlegel, Fassbender, Klein, 2006).…”
Section: Leaders' Dark Personality Its Effect On Leadership and Orgamentioning
confidence: 99%